2020
DOI: 10.1038/s41467-019-14083-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced JunD/RSK3 signalling due to loss of BRD4/FOXD3/miR-548d-3p axis determines BET inhibition resistance

Abstract: BET bromodomain inhibitors (BETi), such as JQ1, have been demonstrated to effectively kill multiple types of cancer cells. However, the underlying mechanisms for BETi resistance remain largely unknown. Our evidences show that JQ1 treatment evicts BRD4 from the FOXD3-localized MIR548D1 gene promoter, leading to repression of miR-548d-3p. The loss of miRNA restores JunD expression and subsequent JunD-dependent transcription of RPS6KA2 gene. ERK1/2/5 kinases phosphorylate RSK3 (RPS6KA2), resulting in the enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Other studies reported JunD expression was increased in hearts from diet-induced obese mice, and regulated PPARc signaling leading to cardiac damage (44). miR-548d-3p directly targets JunD and loss of miR-548d-3p enhances JunD/RSK3 signaling in the chemotherapy resistant of breast cancer (45). JunD as a member of the transcription factors Activated Protein-1 (AP-1) family, is essential as a major gatekeeper in cell proliferation and fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported JunD expression was increased in hearts from diet-induced obese mice, and regulated PPARc signaling leading to cardiac damage (44). miR-548d-3p directly targets JunD and loss of miR-548d-3p enhances JunD/RSK3 signaling in the chemotherapy resistant of breast cancer (45). JunD as a member of the transcription factors Activated Protein-1 (AP-1) family, is essential as a major gatekeeper in cell proliferation and fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Non coding RNA (ncRNA) has been once considered as the "noise" of human genome transcription, which has no biological effects. With the development of high-throughput sequencing technology and in-depth research, more and more ncRNAs, especially miRNA and lncRNA, have been found to play very important roles in epigenetic regulation and take part in the occurrence and development of multiple diseases [22][23][24]. Although there have been some reports about ncRNAs in HSCR, its mode of action and mechanism still need further study [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…JQ1 is the first drug that has been identified to inhibit the expression of C-MYC gene, an important oncogene, and had been thought to be a breakthrough in the field of tumor therapy. However, studies have indicated frequent resistance to JQ1 appeared in numerous tumor cells, so the exploration of resistance mechanism and combination therapy regimen have become the new hotspot [7][8][9][10][11]. The combination therapy focusing on the function of macrophages is few.…”
Section: Discussionmentioning
confidence: 99%
“…Many signal pathways are involved in subsequent downregulation of MYC-dependent genes and they interweave into a complicated network, thus various compensatory transcription mechanisms also evolved, leading to the resistance to JQ1 [6]. As the resistance to JQ1 appeared increasingly often, some studies have revealed the mechanism of resistance to JQ1, which varies in different tumor cells [7][8][9][10][11]. To improve the efficacy of JQ1, people try to combine JQ1 with other drugs and the regimens are destined to differ in different tumors.…”
Section: Introductionmentioning
confidence: 99%